Insuring Peace: Index-Based Livestock Insurance, Droughts, and Conflict - Kai Gehring; Paul Schaudt (Center for Economic Studies and ifo Institute (CESifo), 2023)
We provide novel evidence of how an innovative market-based solution using remote-sensing technology can mitigate conflict. Droughts are a major driver of conflict in Africa, particularly between nomadic pastoralists and sedentary farmers, and climate change is predicted to intensify this problem. The Index-Based Livestock Insurance (IBLI) scheme piloted in Kenya provides automated, preemptive payouts to pastoralists affected by droughts. Combining plausibly exogenous variation in rainfall and the staggered roll-out of IBLI in Kenya over the 2001-2020 period, we find that IBLI strongly reduces drought-induced conflict. One key mechanism is that insured pastoralists travel less far away from their ancestral homelands, reducing conflicts over scarce resources in contested areas. This suggests that market-based solutions are a promising pathway to mitigate conflict beyond difficult institutional reforms and raises the question of how governments can support the adoption of such schemes for underprivileged groups through subsidies or other campaigns.
Keywords: D74; G22; G52; O13; Q34; Q54; 330; conflict; conflict resolution; climate change; droughts; pastoralism; insurance; ICT; resources